2002
DOI: 10.1002/jmr.553
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of an anti‐estradiol antibody by site‐directed mutagenesis and molecular modelling: modulation of binding properties and prominent role of the VL domain in estradiol recognition

Abstract: The high-affinity monoclonal anti-estradiol antibody 9D3 presents a specificity defect towards estradiol-3-sulphate and 3-glucuronide conjugates incompatible with use in direct immunoassays. The corresponding single-chain variable fragment (scFv), cloned and produced in E. coli, exhibited a 10-fold lower affinity for estradiol (K(a)=1.2 x 10(9) M (-1)) and a slightly increased specificity defect for the 3-position. Site-directed mutagenesis revealed critical residues involved in estradiol recognition and produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…26 In particular, he showed that the principal determinant of the binding affinity is the change in compactness and folding increment of the two antibody chains. This effect was also observed in more general studies by Getzoff et al, 36 Pellequer et al, 37 and Coulon et al 38 and is likely related to the hydrophobic interactions between the steroids and DB3. 26 While the above studies support our hypothesis, a more extensive analysis of proteins from multiple families is necessary before we can ascertain the generality of this trend.…”
Section: Folding Of Top7 Proteinsupporting
confidence: 75%
See 1 more Smart Citation
“…26 In particular, he showed that the principal determinant of the binding affinity is the change in compactness and folding increment of the two antibody chains. This effect was also observed in more general studies by Getzoff et al, 36 Pellequer et al, 37 and Coulon et al 38 and is likely related to the hydrophobic interactions between the steroids and DB3. 26 While the above studies support our hypothesis, a more extensive analysis of proteins from multiple families is necessary before we can ascertain the generality of this trend.…”
Section: Folding Of Top7 Proteinsupporting
confidence: 75%
“…This is supported by recent studies by Estrada and others who have noted a strong correlation between the energy of the folded structure and degree of compactness. 26,[36][37][38] Nonetheless, a comprehensive analysis of a large database of protein structures is necessary before one can establish this relationship. We plan to address this question as well as the applicability of the folding profile to characterize different families of folds in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…We have confirmed that a V L -domain protein derived from Ab#E4-4 alone had significant affinity to E 2 -7−BSA conjugates (data not shown). It should be noted that, in another mouse monoclonal anti-E 2 antibody (9D3), the V L domain played a prominent role in E 2 recognition …”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that, in another mouse monoclonal anti-E 2 antibody (9D3), the V L domain played a prominent role in E 2 recognition. 38 This scFv had a remarkably long 15-residue CDR H3 (the highest occurrence of CDR H3 residues in mouse antibodies was reported to be 9). 39 However, only a few residues of this CDR, located on the border between FRs (e.g., Glu H95 , Arg H96 , and Leu H100g ), seemed to be close to E 2 , and the residues on the tip were not likely.…”
Section: Construction Of the Second Library And Isolation Of Scfvmentioning
confidence: 97%
“…In another study, the VL domain of antibody F11 preserved the antigen-binding function in the absence of VH partner and fusion to barnase increased the solubility of the VL domain both in vivo and in vitro [22,23] . Coulon et al showed that the VL domain of anti-estradiol mAb 9D3 played a prominent role in estradiol recognition [24] . The studies of Twan et al further suggested that it was feasible to create specific single VL domain to diverse targets as is the case for single VH domains in their study [25] .…”
Section: Discussionmentioning
confidence: 99%